The Role Of School Radio In Developing The Value System Of Basic And Secondary Students From The Perspectives Of Teachers In Ajloun Governorate / Sakhrah District (Journal of Namibian Studies : History Politics Culture, 2023)
This study addresses the role of school radio in developing the value system of basic and secondary students from the perspectives of teachers in the Sakhrah District. To achieve the objectives of this study, the descriptive-analytical design was employed. The population of the study consisted of (2830) teachers working at the Ajloun directorate of education, while the study sample consisted of (233) school teachers selected purposefully. The results showed that the role of school radio in developing the value system regarding school discipline was high, and it was also high regarding patriotism from teachers' perspectives.